Resistance prevalence profile of Klebsiella pneumoniae in the Intensive Care Units of AlShatby Pediatric Hospital, Alexandria, Egypt - Bassma H. Elwakil; Safaa M. Ali; Soad F. Hafez; Adnan A. Bekhit; Moustafa Y. El-Naggar; Zakia A. Olama (Novel Research in Microbiology Journal)
Klebsiella pneumoniae has been identified as an opportunistic pathogen associated with both communityacquired and nosocomial infections mainly among patients admitted to the Intensive care units (ICUs). Some resistant genes were transferred vertically or horizontally within many microbial communities, directly between bacteria through plasmids or integrin. Different techniques including; phenotypic and genetic ones were used to evaluate the presence of β-lactamases among the isolated strains of K. pneumoniae. This bacterial species is the most commonly isolated pathogen (95 isolates) from all the examined samples (51.35%). Current results revealed that 30 and 14 strains of K. pneumoniae are positive to Extended spectrum β-lactamase (ESBL) production, and AmpC β-lactamase producers, respectively. On the other hand, modified carbapenem inactivation and modified Hodge test (MHT) were used to assess the carbapenem resistant strains. It is observed that all the β-lactamase producers’ strains are also carbapenemase producers, whereas only nine strains (30%) are MHT positive. The Polymerase Chain Reaction (PCR) technique revealed that TEM, BETA, NDM and IPM genes are found on the bacterial plasmid (100%). However the presence of the β-lactamase genes on the bacterial DNA varied among the different strains. The presence of the resistance genes on the bacterial plasmid may signify the resistance acquired upon the previous exposure of this bacterium to the different antibiotics. The aims of the current work were to isolate K. pneumonia from Al-Shatby hospital ICUs, to determine the incidence of its β-lactamases, and to decide the frequency of acquisition of 12 different genes among ESBL K. pneumoniae isolates.